[Pigeon Point] - (:unkn) unknown (Norman Parkinson, 2011)
Description printed on the back of the postcard: "Seen through the coconut trees at Pigeon Point, Tobago, sailfish which can be hired by the hour. The water is so warm, the sea so calm, the sand so coral white that happiness and exhilaration are ever present whatever your age or interests."
Colour: Coloured; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Beaches--Trinidad and Tobago; Boats and boating--Trinidad and Tobago; Beachgoers--Trinidad and Tobago; [1995]; Coconut palm--Trinidad and Tobago; Seashore--Trinidad and Tobago; Coasts--Trinidad and Tobago; Bathing beaches--Trinidad and Tobago